2016
DOI: 10.1177/0021998316672001
|View full text |Cite
|
Sign up to set email alerts
|

Process improvement for out-of-autoclave prepreg curing supported by in-situ strain monitoring

Abstract: Vacuum-bag-only curing is an attractive out-of-autoclave method as an alternative to conventional autoclave curing. Previous extensive researches provided great insight into void formation during the vacuum-bag-only method and these findings are reflected in current vacuum-bag-only cure cycles to minimize void content. Cure process can be further improved by taking into consideration cure-induced residual stress/strain. The present paper proposed a residual stress/strain reduction method and evaluated its effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Hence, excessive and unnecessary corner suppression is avoided. A similar finding is reported by Yijia Ma et al [26]; the CoV results reported in this study are in good agreement to theirs.…”
Section: Thickness Variation Of Laminated Compositessupporting
confidence: 94%
“…Hence, excessive and unnecessary corner suppression is avoided. A similar finding is reported by Yijia Ma et al [26]; the CoV results reported in this study are in good agreement to theirs.…”
Section: Thickness Variation Of Laminated Compositessupporting
confidence: 94%
“…[ 20,21 ] Studies have shown that the MRCC for commercially available prepregs could further improve mechanical properties by considering residual stress/strain induced during curing. [ 21–23 ] Takagaki et al [ 23 ] proposed two new improved cure cycles by examining in situ cure‐induced residual stress/strain of a commercially available prepreg. They demonstrated that after C‐stage, the resin is vitrified and 100% degree of cure (DOC) was achievable.…”
Section: Introductionmentioning
confidence: 99%
“…Because T650-35 8HS laminates were cured above T g , during cure, polymer chains were in a rubbery state with high mobility and short relaxation time, allowing relaxation of stress induced by cure shrinkage. [5][6][7] Thus, the internal stress at 371 C was assumed to be zero. The thermal stress at a temperature (T) in a cross-ply region was calculated by integrating equation 2 Numerical calculation of thermal stress in T650-35 8HS/ PMR-15 composites revealed that the thermal stress in the crimped region was 12% greater than in the cross-ply region.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…Thus, it is generally assumed that composites are in a stress-free state during cure above T g . 6,7 After cure, the polymer matrix is vitrified and bonded to the fibers. Coefficients of thermal expansion (CTEs) of polymers generally are much greater than those of carbon fibers.…”
Section: Introductionmentioning
confidence: 99%